2010
DOI: 10.1111/j.1099-0860.2010.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Children’s Social and Emotional Well-being: Does ‘Having a Say’ Matter?

Abstract: This article argues the importance of ensuring initiatives aimed at improving children’s social and emotional well‐being are based on sound participatory principles. The discussion posits links between the recognition of children, dialogic approaches to participation, changing conceptualisations of children and childhood, and children’s well‐being. It explores these links in light of one particular initiative, Seasons for Growth (Graham, 1996, 2002, Seasons for Growth; Loss and Grief Education Program. MacKill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
2
31
0
1
Order By: Relevance
“…Through these Circle Time techniques, the facilitators aimed to 'deprivilige' their adult status and avoid leading the children in their responses. Thus the facilitator role was principally to 'scaffold' the conversation process between the children of their shared experience (Graham & Fitzgerald, 2011). Children were given labels with a number to wear and asked to refer to each other by their numbers whilst the audiotape was recording and told that it was not necessary to reveal personal details (Day et al, 2006).…”
Section: Circle Time Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these Circle Time techniques, the facilitators aimed to 'deprivilige' their adult status and avoid leading the children in their responses. Thus the facilitator role was principally to 'scaffold' the conversation process between the children of their shared experience (Graham & Fitzgerald, 2011). Children were given labels with a number to wear and asked to refer to each other by their numbers whilst the audiotape was recording and told that it was not necessary to reveal personal details (Day et al, 2006).…”
Section: Circle Time Protocolmentioning
confidence: 99%
“…Given the discrepancies that can exist between accounts of mental health difficulties and therapies between child, parent and professional, it is essential that the unique contribution of the child or young person is actively sought using methods that are salient to them (DiBartolo & Grills, 2006). Moreover, this participatory approach may be critical for the growth of identity and have a beneficial impact on children's social-emotional health (Graham & Fitzgerald, 2011). Therefore, there remains a need for a better understanding of how children experience school-based and other child related services so their views can inform future intervention development, delivery and evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…It also conveyed the interviewer's acceptance of Tanja's experiences and emotions (cf. Graham & Fitzgerald, 2011). Finally, the interviewer also formulated her comments discreetly, especially when the talk concerned Tanja's parental problem.…”
Section: Discussionmentioning
confidence: 99%
“…Lightfoot and Sloper () and reported the therapeutic benefits of consulting physically disabled or chronically ill children. Graham and Fitzgerald () found that participation enabled young people to be more adaptable which, in turn, promoted their emotional well‐being. Pupil empowerment and enhanced self esteem was a major theme emerging from the action research by Jelly and colleagues () when they worked on enhancing the participation of children with SEN.…”
Section: The Visionmentioning
confidence: 99%